2013
DOI: 10.1254/jphs.12275fp
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 Inhibits Collagen Secretion From Lung Fibroblasts by Activating the DP Receptor

Abstract: Abstract. Lung fibroblasts are responsible for collagen secretion during normal tissue repair and the development of fibrosis. Many other prostaglandins have been reported to regulate collagen synthesis in lung fibroblasts, but the role of prostaglandin D 2 (PGD 2 ) is unknown. In this study, we investigated the effect of PGD 2 on type I collagen secretion in human lung fibroblasts. Pretreatment with PGD 2 (0.1 -10 μM, 1 h) significantly attenuated type I collagen secretion to the cell supernatant induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…studies have demonstrated that human lung fibroblasts are highly responsive to prostaglandin E 2 (PGE 2 ), prostaglandin D 2 (PGD 2 ), and prostacyclin (PGI 2 ) in terms of cAMP activation and inhibition of myofibroblast activation (13,34,38). We also showed that PKA can be rapidly activated by endothelin-1 or by ATP through cyclooxygenase (COX)-mediated prostanoid synthesis in vascular smooth muscle cells (30,35,37).…”
Section: Ep 2 Prostaglandin Receptors Mediate Regulation Of Myofibrobmentioning
confidence: 89%
“…studies have demonstrated that human lung fibroblasts are highly responsive to prostaglandin E 2 (PGE 2 ), prostaglandin D 2 (PGD 2 ), and prostacyclin (PGI 2 ) in terms of cAMP activation and inhibition of myofibroblast activation (13,34,38). We also showed that PKA can be rapidly activated by endothelin-1 or by ATP through cyclooxygenase (COX)-mediated prostanoid synthesis in vascular smooth muscle cells (30,35,37).…”
Section: Ep 2 Prostaglandin Receptors Mediate Regulation Of Myofibrobmentioning
confidence: 89%
“…Our group previously showed that PGD 2 attenuates collagen secretion induced by TGF-β in human lung fibroblasts by activating D-prostanoid (DP) receptor [31]. Another group demonstrated that PGD 2 inhibits proliferation of mouse lung fibroblasts via DP receptor [32].…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental model of skin wound healing, PGD 2 and its degradation products were proposed to reduce inflammation via the activation of PPARγ, thus contributing to resolution after the inflammatory phase of tissue repair. In addition to the potential proresolving effects of PGD 2 metabolites, PGD 2 itself was reported to suppress collagen production and the recruitment of pulmonary fibroblasts by engaging its high affinity receptor DP1 . This suggests that despite its proinflammatory roles in type 2 immune responses, PGD 2 can act as a negative regulator of airway remodeling.…”
Section: Roles Of Eicosanoids In Tissue Repairmentioning
confidence: 99%